An analysis of the professional identity and experiences of clinical psychologists in South Africa - Shnier, Tarryn Kaela (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
The discipline of psychology, and the profession of clinical psychology in South Africa has made marked strides over the nearly 30 years since the end of the apartheid era. However, there is little known about the professional identity and experiences of clinical psychologists in South Africa. This study involved conducting a critical incident analysis of the experiences of 410 clinical psychologists in South Africa, in order to identify possible commonality in experiences and what meaning these experiences have for the professional identity of clinical psychologists in South Africa. Findings suggest that professional identity is greatly influenced by experiences involving interactions with mental health care users, and experiences working within multidisciplinary teams. These findings are discussed in connection with existing literature that details concepts of professional identity and South African psychology, in order to establish clarity on the professional identity of clinical psychologists in South Africa.
Keywords: Psychology -- South Africa; Clinical psychologists -- South Africa; Critical incident technique; Psychology -- Practice -- South Africa; Identity (Psychology); Empirical